Examining intersectionality and inclusivity in geosciences education research: A synthesis of the literature 2008–2018. Issue 4 (2nd October 2019) - Mattheis, Allison; Murphy, Megan; Marin-Spiotta, Erika
Abstract: This article reviews geoscience education research published since the December 2007 "Broadening Participation" issue of the Journal of Geoscience Education to examine how research in the field has taken up—or not—calls for greater inclusivity. We also applied recent calls to actively confront and lessen reports of discrimination and harassment in the sciences and looked for evidence of how these goals are included in geoscience education research. This synthesis of the extant literature in geoscience education research was guided by a framework that draws from the concept of intersectionality (Collins, 2015 ; Crenshaw, 1991 ) and interventions that can build learning environments that provide physical and psychological safety for diverse students, educators, and field professionals synthesized by a 2018 report from the National Academies of Science, Engineering, and Medicine. We identified three primary themes in the literature reviewed and illustrate these with examples from published articles: (a) increased challenges to science as neutral, (b) continued assumptions of meritocracy in higher education, and (c) assimilation as representation. We also highlight exemplary articles that were most closely aligned with our conceptual framework, and then present three recommendations for future research efforts. A key goal of the present article is to call on researchers to more deeply consider the role of social identities in studies of geoscience education.